A PZT-PVDF stacked transducer for short-pulse ultrasound therapy and monitoring - Jiang,Z; Dickinson,RJ; Hall,TL; Choi,JJ (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control, 2021)
Therapeutic ultrasound technologies using microbubbles require a feedback control system to perform the treatment in a safe and effective manner. Current feedback control technologies utilize the microbubble’s acoustic emissions to adjust the treatment acoustic parameters. Typical systems use two separated transducers: one for transmission and the other for reception. However, separating the transmitter and receiver leads to foci misalignment. This limitation could be resolved by arranging the transmitter and receiver in a stacked configuration. Taking advantage of an increasing number of short-pulse-based therapeutic methods, we have constructed a PZT-PVDF stacked transducer design that allows the transmission and reception of short-pulse ultrasound from the same location. Our design had a piston transmitter composed of a PZT disc (1 MHz, 12.7 mm in diameter), a backing layer, and two matching layers. A layer of Polyvinylidene fluoride (PVDF) (28 μm in thickness, 12.7 mm in diameter) was placed at the front surface of the transmitter for reception. Transmission and reception from the same location was demonstrated in pulse-echo experiments where PZT transmitted a pulse and both PZT and PVDF received the echo. The echo signal received by the PVDF was 0.43 μs shorter than the signal received by the PZT. Reception of broadband acoustic emissions using the PVDF was also demonstrated in experiments where microbubbles were exposed to ultrasound pulses. Thus, we have shown that our PZT-PVDF stack design has unique transmission and reception features that could be incorporated into a multi-element array design that improves focal superimposing, transmission efficiency, and reception sensitivity.